The art of kelingkan embroidery as a catalyst for the development of the creative industry - Zainal Amri, Norhasliyana Hazlin; Haron, Hamdzun; Samian, Abdul Latif (2018)
Kelingkan is a unique handicraft that uses metal strips gilt with gold or silver that is embroidered onto the surface of a soft fabric. The intricacy of this type of embroidery requires a high degree of detail and expertise. In Malaysia, kelingkan embroidery is practised on a small scale and sold for a high sum. However, how far is kelingkan embroidery known today and can it become a catalyst for the development of the creative industry? This study is conducted in the descriptive qualitative method via field work, namely observational interviews with embroiderers and studies of collections. As a result, this study has found that there are 3 states with active embroiderers that are still able to sell their kelingkan shawls or selayah for more than RM1000 per piece. In addition, the beauty and creativity of kelingkan embroidery has continued to attract even more members of the community to purchase kelingkan items, as they are used in important official ceremonies. This study has also concluded that an increase in the number of embroiderers will help to generate revenue and increase the production of kelingkan products to aid in the development of the creative industry. As an implication, this study can be used a source of knowledge and income, so that this art form will be sustained and be a source of income for the Malay community.